2021
DOI: 10.1038/s41598-021-93008-y
|View full text |Cite
|
Sign up to set email alerts
|

Salivary citrullinated proteins in rheumatoid arthritis and associated periodontal disease

Abstract: Periodontal disease (PD) can be an important precipitating factor in the production of citrullinated proteins. Its importance is emphasized, but it is not the only way to produce citrullinated proteins. The aim of the current study was to determine the periodontal conditions and the salivary citrullinated protein content in patients with rheumatoid arthritis (RA) compared to healthy controls. We also wished to correlate citrullinated protein levels in the saliva and serum biomarkers with the periodontal status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
12
0
5
Order By: Relevance
“…With respect to the presence of citrullinated peptides in human saliva, Tar et al developed an assay system to immobilize saliva samples on membranes and perform the semi-quantification of total citrullinated peptides using AMC antibodies, and reported that the quantities of total citrullinated peptides in saliva from patients with RA and healthy controls were comparable [ 24 ]. Because their assay system was based on a dot-blot method, the details of salivary citrullinated peptides remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the presence of citrullinated peptides in human saliva, Tar et al developed an assay system to immobilize saliva samples on membranes and perform the semi-quantification of total citrullinated peptides using AMC antibodies, and reported that the quantities of total citrullinated peptides in saliva from patients with RA and healthy controls were comparable [ 24 ]. Because their assay system was based on a dot-blot method, the details of salivary citrullinated peptides remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our study objectives, we need to choose a suitable tissue to analyze all diseases. Some potential issues such as whole blood ( 111 , 112 ) and the gut microbiome ( 113 ), are suitable for our study. The ReDisX framework could be extended and improved in the future using multimodal data besides mRNA expressions such as methylation and miRNA interference.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our study objectives, we need to choose a suitable tissue to analyze all diseases. There are a few potential issues such as whole blood (Anaparti et al, 2017), saliva (Tar et al, 2021), and the gut microbiome (Shreiner et al, 2015) those are suitable for our study. In the future, the ReDisX framework could be extended and improved using multimodal data besides mRNA expressions such as methylation, and miRNA interference.…”
Section: Redisx Is the Robust Scalable Reproducible Frameworkmentioning
confidence: 99%